Pruners: Providing reproducibility for uncovering non-deterministic errors in runs on supercomputers. (September 2019) - Sato, Kento; Laguna, Ignacio; Lee, Gregory L; Schulz, Martin; Chambreau, Christopher M; Atzeni, Simone; Bentley, Michael; Gopalakrishnan, Ganesh; Rakamaric, Zvonimir; Sawaya, Geof; Protze, Joachim; Ahn, Dong H
Large scientific simulations must be able to achieve the full-system potential of supercomputers. When they tap into high-performance features, however, a phenomenon known as non-determinism may be introduced in their program execution, which significantly hampers application development. Pruners is a new toolset to detect and remedy non-deterministic bugs and errors in large parallel applications. To show the capabilities of Pruners for large application development, we also demonstrate their early usage on real-world production applications.